Carbon electrode aerogel material, electrode and preparation method thereof
By using specific proportion combinations of carbon nanotubes, activated carbon and graphene oxide in smart mobile charging piles to form carbon electrode aerogel materials with high specific capacitance, the problems of low energy density and small specific capacitance are solved, and high Discharge power and long cycle life electrode material.
Patent Information
- Application Number
- CN202411477619.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-07
AI Technical Summary
The energy density of existing supercapacitors is low, resulting in an increase in the volume and weight of mobile charging piles, affecting their promotion. The specific capacitance of existing carbon electrode materials is smaller, which cannot meet the high discharge power and long cycle use of intelligent mobile charging piles. Life expectancy.
Using a specific proportion combination of materials such as carbon nanotubes, activated carbon and graphene oxide, aerogel material is formed by foaming and freeze-drying, and activated in potassium hydroxide solution to form a carbon electrode aerogel material with high specific capacitance. .
The specific capacitance of the electrode is improved, the charge capacity and conductivity are increased, the volume and weight of the electrode are reduced, and the high discharge power and long cycle life requirements of intelligent mobile charging piles are met.
Smart Images

Figure BDA0005096531330000091 
Figure BDA0005096531330000101
Abstract
Description
Technical Field
[0001] The invention relates to a carbon electrode aerogel material, an electrode and a preparation method thereof. Background Art
[0002] As the market share of new energy vehicles increases, the demand for supporting basic charging facilities is also increasing. However, some communities have insufficient transformer capacity and cannot install charging piles. In addition, the disordered charging behavior of new energy vehicles often highly overlaps with the daily electricity load curve of residents, which affects the operation of the distribution network and seriously affects the safety and stability of power supply. Smart mobile charging piles can operate off the grid and will complement fixed charging piles to become basic charging facilities. Smart mobile charging piles need to have high discharge power and long cycle life. Supercapacitors can be used as the core device of mobile charging piles. However, the energy density of supercapacitors is generally low, which will increase the volume and weight of mobile charging piles, which is not conducive to the promotion of mobile charging piles.
[0003] CN105448540A discloses a method for preparing a highly conductive activated carbon electrode for a supercapacitor, comprising the following steps: adding an activated carbon raw material to a graphene oxide solution, reacting at 80-100°C for 1-10 hours under ultrasonic conditions, and obtaining a mixture solution after the reaction is completed; adding the mixture solution to a polytetrafluoroethylene container, adding a catalyst, and reacting at 80-200°C for 1-10 hours after sealing, washing with distilled water after the reaction is completed, and drying at 80-100°C to obtain a carbon electrode. The specific capacitance prepared by this method is relatively low.
[0004] CN106531459A discloses a method for preparing a graphene / activated carbon composite film, wherein the activated carbon is mixed with a graphene oxide dispersion after acid modification, the graphene / activated carbon mixture is then frozen, the solid mixture after freezing is subsequently dried, the graphene oxide is thermally reduced to obtain a graphene / activated carbon aerogel, and finally the graphene / activated carbon aerogel is mechanically pressed by a roller press or a tablet press to obtain a graphene / activated carbon composite film. The composite film has a small specific capacitance.
[0005] CN11681882A discloses a method for improving the electrochemical performance of a composite carbon material, wherein the composite carbon material is coated on a current collector to obtain an electrode sheet; the composite carbon material includes graphene oxide, carbon nanotubes and activated carbon. The electrode sheet is placed in a magnetic field with a magnetic field strength of 0.05 to 0.25 T. The electrode sheet is a non-flexible material and has a small specific capacitance.
[0006] CN103050294A discloses a method for preparing an activated carbon / carbon nanotube composite aerogel electrode material, wherein carbon nanotubes ultrasonically dispersed in an aqueous solution are placed in a current collector, hydroquinone and formaldehyde are added, and a catalyst and a structure directing agent are added, and the reaction is carried out at 60 to 100°C to obtain a phenolic resin / carbon nanotube composite gel, which is freeze-dried to form a phenolic resin / carbon nanotube composite aerogel. The phenolic resin / carbon nanotube composite aerogel is carbonized under the protection of an active gas to form an activated carbon / carbon nano composite aerogel, the current collector is extracted, and excess carbon is removed to obtain an activated carbon / carbon nanotube composite aerogel electrode material. The specific capacitance of the electrode material is small. Summary of the invention
[0007] In view of this, one object of the present invention is to provide a method for preparing a carbon electrode aerogel material, and the carbon electrode aerogel material obtained by the preparation method can effectively improve the specific capacitance of the electrode. Another object of the present invention is to provide a carbon electrode aerogel material. Another object of the present invention is to provide an electrode having a higher specific capacitance. Another object of the present invention is to provide a method for preparing an electrode.
[0008] In one aspect, the present invention provides a method for preparing a carbon electrode aerogel material, comprising the following steps:
[0009] (1) stirring and foaming a raw material containing carbon nanotubes, activated carbon, graphene oxide, a reducing agent, an animal protein foaming agent and water to obtain a foam; keeping the foam at 70 to 120° C. to obtain a wet gel; and freezing the wet gel to obtain a dry gel;
[0010] The mass ratio of carbon nanotubes, activated carbon and graphene oxide is 1:(20-28):(0.7-1.6), and the mass ratio of graphene oxide to animal protein foaming agent is 1:(0.3-0.8);
[0011] (2) The dried gel is immersed in a potassium hydroxide solution with a concentration of 3 to 25 wt %; after drying, it is activated at 450 to 850° C. in an inert atmosphere to obtain a carbon electrode aerogel material.
[0012] According to the preparation method of the present invention, preferably, the reducing agent is ascorbate, and the mass ratio of graphene oxide to the reducing agent is 1:(1-3);
[0013] In the raw material of step (1), the amount of graphene oxide used is 0.3 to 0.9 g based on 100 mL of water.
[0014] According to the preparation method of the present invention, preferably, the diameter of the carbon nanotubes is ≤15nm, the length of the carbon nanotubes is 5-15μm; the specific surface area of the activated carbon is 1500-2500m 2 / g, the pore volume of activated carbon is 0.8-1.2mL / g; the oxygen-carbon molar ratio of graphene oxide is 0.45-0.65, the sheet diameter of graphene oxide is 15-50μm, and the sheet thickness of graphene oxide is ≤10nm.
[0015] According to the preparation method of the present invention, preferably, in step (1), the insulation time is 3 to 9 hours and the freezing temperature is -30 to -5°C.
[0016] According to the preparation method of the present invention, preferably, in step (2), the dried gel is washed and then immersed in a potassium hydroxide solution; the drying temperature is 70-105°C.
[0017] The preparation method according to the present invention preferably further comprises the following steps:
[0018] The activated gel obtained by activation is washed with water and then dried; the dried activated gel is pressed into sheets under the condition of 5-20 MPa to obtain a carbon electrode aerogel material.
[0019] On the other hand, the present invention provides a carbon electrode aerogel material, which is prepared by the above preparation method.
[0020] In another aspect, the present invention provides an electrode, comprising a current collector layer and a carbon electrode aerogel material layer formed by the carbon electrode aerogel material according to claim 7, wherein the carbon electrode aerogel material layer is attached to the surface of the current collector layer.
[0021] According to the electrode of the present invention, preferably, the current collector layer is aluminum foil.
[0022] In another aspect, the present invention provides the above-mentioned electrode preparation method, comprising the following steps:
[0023] The carbon electrode aerogel material is laminated to the current collector and then pressed to obtain an electrode.
[0024] The present invention uses specific amounts of carbon nanotubes, activated carbon, graphene oxide and animal protein foaming agent to make the carbon electrode aerogel material have a three-dimensional network structure of appropriate macropores, mesopores and micropores. It provides an effective path for the rapid movement of electrolyte ions, increases the specific surface area of the aerogel material, increases the charge capacity, and increases the specific capacitance. The present invention uses a potassium hydroxide solution of a specific concentration as an activator and activates it at an appropriate temperature, thereby increasing the specific surface area of the catalyst, and does not affect the pore structure of the aerogel, thereby increasing the specific capacitance. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0026] <Method for preparing carbon electrode aerogel material>
[0027] The method for preparing the carbon electrode aerogel material of the present invention comprises the following steps: (1) a step of preparing gel; and (2) a step of activating.
[0028] Steps for preparing gel
[0029] The present invention stirs and foams raw materials containing carbon nanotubes, activated carbon, graphene oxide, a reducing agent, an animal protein foaming agent and water to obtain a foamed body; the foamed body is kept warm to obtain a wet gel; and the wet gel is frozen to obtain a dry gel. In some embodiments, the raw materials are composed of carbon nanotubes, activated carbon, graphene oxide, a reducing agent, an animal protein foaming agent and water.
[0030] Carbon nanotubes and activated carbon can be added to the graphene oxide aqueous dispersion, dispersed evenly by ultrasonication, and then a reducing agent and an animal protein foaming agent are added to stir and foam to obtain a foamed body. This helps to fill and distribute the carbon nanotubes and activated carbon in the three-dimensional network structure composed of graphene, and helps to entangle the carbon nanotubes with the activated carbon to form a proper pore structure, thereby improving the specific capacitance.
[0031] In the present invention, the mass ratio of carbon nanotubes to activated carbon is 1:(20-28); preferably 1:(22-26); more preferably 1:(24-25). The present invention finds that the amount of carbon nanotubes and activated carbon has an important influence on the specific capacitance. Within the amount range of the present invention, both the specific surface area and the higher conductivity can be achieved, thereby improving the specific capacitance.
[0032] The diameter of the carbon nanotube may be ≤15 nm and the length of the carbon nanotube may be 5 to 15 μm.
[0033] The specific surface area of activated carbon can be 1500~2500m 2 / g. The pore volume of activated carbon can be 0.8 to 1.2 mL / g.
[0034] In the present invention, the mass ratio of carbon nanotubes to graphene oxide is 1:(0.7-1.6); preferably 1:(1-1.5); more preferably 1:(1.3-1.4). This helps to form a proper pore structure.
[0035] The oxygen-carbon molar ratio of graphene oxide may be 0.45 to 0.65. The sheet diameter of graphene oxide may be 15 to 50 μm. The sheet thickness of graphene oxide may be ≤10 nm.
[0036] In the present invention, the mass ratio of graphene oxide to animal protein foaming agent is 1:(0.3-0.8); preferably 1:(0.4-0.7); more preferably 1:(0.5-0.6). This helps to form a proper pore structure and improve specific capacitance.
[0037] The animal protein foaming agent can be one or a combination of hydrolyzed animal hoof keratin foaming agent, hydrolyzed animal hair protein foaming agent, hydrolyzed blood collagen foaming agent, and composite animal protein foaming agent. Preferably, the animal protein foaming agent is FP-50A animal protein foaming agent.
[0038] In the present invention, the mass ratio of graphene oxide to reducing agent can be 1:(1-3); preferably 1:(1.5-2.5); more preferably 1:(2-2.2). The reducing agent is preferably ascorbate; more preferably sodium ascorbate. In this way, graphene oxide can be reduced to improve the conductivity and specific capacitance.
[0039] In the raw materials, based on 100 mL of water, the amount of graphene oxide used is 0.3 to 0.9 g; preferably 0.4 to 0.7 g; more preferably 0.5 to 0.6 g.
[0040] The raw materials are stirred and foamed at a rotation speed of 5000 to 20000 rpm; preferably, at a rotation speed of 9000 to 16000 rpm.
[0041] The insulation temperature is 70 to 120° C., preferably 80 to 110° C., and more preferably 90 to 100° C. The insulation time can be 3 to 9 hours, preferably 4 to 8 hours, and more preferably 5 to 7 hours.
[0042] The freezing temperature can be -30 to -5°C, preferably -25 to -10°C, and more preferably -20 to -15°C. The freezing time can be 3 to 20 hours, preferably 5 to 15 hours, and more preferably 8 to 12 hours. In this way, the wet gel can be fully dried without affecting the pore structure of the product.
[0043] Before freezing, the wet gel can be washed to remove the excess reducing agent and animal protein foaming agent on the wet gel. Specifically, the wet gel can be washed with water.
[0044] Activation steps
[0045] The invention immerses the dried gel in a potassium hydroxide solution with a concentration of 3-25 wt %; after drying, the dried gel is activated at 450-850 DEG C in an inert atmosphere to obtain a carbon electrode aerogel material.
[0046] The concentration of potassium hydroxide solution is 3-25wt%, preferably 5-20wt%, and more preferably 10-15wt%. The immersion time can be 2-15min, preferably 3-10min, and more preferably 5-8min. This can increase the surface area of the aerogel material without affecting the pore structure of the aerogel, thereby increasing the specific capacitance.
[0047] The drying temperature may be 70 to 120°C, preferably 80 to 110°C, and more preferably 90 to 100°C.
[0048] The inert atmosphere can be selected from one or more of nitrogen, helium, neon, and argon; preferably, the inert atmosphere is nitrogen.
[0049] The activation temperature can be 450-850°C, preferably 500-800°C, and more preferably 550-650°C. The activation time can be 1-5h, preferably 1.5-4h, and more preferably 2-3h. This can increase the surface area of the aerogel material without affecting the pore structure of the aerogel, thereby increasing the specific capacitance.
[0050] In some embodiments, the method further comprises the following steps: washing the activated gel obtained by activation with water and then drying it; pressing the dried activated gel into sheets under the condition of 5-20 MPa to obtain a carbon electrode aerogel material.
[0051] Preferably, the upper and lower surfaces of the dried activated gel are cut off before pressing.
[0052] The pressing pressure is 5 to 20 MPa, preferably 8 to 15 MPa, and more preferably 10 to 12 MPa.
[0053] <Carbon Electrode Aerogel Materials>
[0054] The carbon electrode aerogel material of the present invention is prepared by the above-mentioned preparation method. The obtained carbon electrode aerogel material has abundant pores inside, and the carbon nanotubes wrapped with activated carbon are uniformly filled and distributed in the three-dimensional network structure of the cross-linked graphene sheets, forming macropores, mesopores and micropores. The macropores are formed by cross-linking the graphene sheets and filled with carbon nanotubes and activated carbon, the mesopores are distributed on the graphene sheets and inside the activated carbon, and the micropores are mainly provided by the activated carbon. The interconnected graphene sheet skeleton provides an effective path for the rapid migration of electrolyte ions, the carbon nanotubes improve the overall conductivity of the electrode, and the large specific surface area of the carbon nanotubes and activated carbon increases the charge capacity.
[0055] <Electrode>
[0056] The electrode of the present invention comprises a current collector layer and a carbon electrode aerogel material layer formed by the above-mentioned carbon electrode aerogel material, wherein the carbon electrode aerogel material layer is attached to the surface of the current collector layer. There is no binder between the carbon electrode aerogel material layer and the current collector layer. The carbon electrode aerogel material of the invention can be attached to the surface of the current collector by physical pressing without using a binder, thereby reducing the introduction of impurity elements and improving the specific capacitance.
[0057] In the present invention, the current collector layer is preferably a copper foil.
[0058] The thickness of the carbon electrode aerogel material layer may be 25 to 120 μm, preferably 35 to 85 μm. In certain embodiments, the thickness of the carbon electrode aerogel material layer is 40 to 60 μm.
[0059] The thickness of the current collector layer may be 8 to 15 μm, preferably 9 to 13 μm. In some embodiments, the thickness of the current collector layer is 10 to 12 μm.
[0060] <Electrode Preparation Method>
[0061] The preparation method of the electrode of the present invention comprises the following steps: laminating the carbon electrode aerogel material with the current collector, and then pressing to obtain the electrode.
[0062] The pressing pressure may be 15 to 25 MPa, preferably 17 to 22 MPa.
[0063] Here are the raw materials:
[0064] Carbon nanotubes: diameter ≤15nm, length 5~15μm.
[0065] Activated carbon: specific surface area is 1500~2500m 2 / g, and the pore volume is 0.8~1.2mL / g.
[0066] Graphene oxide: oxygen-carbon molar ratio is 0.45-0.65, sheet diameter is 15-50 μm, and sheet thickness is ≤10 nm.
[0067] Animal protein foaming agent: FP-50A animal protein foaming agent purchased from Liaocheng Jiukun Building Materials Co., Ltd.
[0068] Here is the test method:
[0069] Specific capacitance: In a glove box, the electrode was assembled with a polyethylene microporous membrane into a 2032-type button-type symmetrical capacitor, and a 1 mol / L H2SO4 aqueous solution was used as the electrolyte. A CS310X multi-channel electrochemical workstation was used to perform constant current charge and discharge tests on the capacitor to evaluate the specific capacitance of the electrode, with a voltage range of 0 to 1 V and a current test density of 1 A / g.
[0070] The specific capacitance (C, F / g) is calculated using the following formula:
[0071] C=(I×t) / (ΔV×m)
[0072] Where I is the discharge current (A), t is the discharge time (s), ΔV is the voltage difference between charge and discharge (V), and m is the electrode mass (g).
[0073] Examples 1 to 2 and Comparative Examples 1 to 3
[0074] (1) Add carbon nanotubes and activated carbon to 100 mL of graphene oxide aqueous dispersion and disperse them uniformly by ultrasonication; then add sodium ascorbate and animal protein foaming agent, stir at 12000 rpm until the foam is uniform, and obtain a foam. The foam is kept at 95°C for 6 hours to obtain a wet gel. After the wet gel is washed with deionized water, the wet gel is frozen at -20°C for 10 hours, and then thawed to obtain a dry gel.
[0075] (2) The dried gel was immersed in a potassium hydroxide solution for 6 minutes, and then dried at 95°C to obtain an immersed gel. The immersed gel was activated at 600°C in a nitrogen atmosphere for 2 hours to obtain an activated gel. The activated gel was washed with deionized water until the eluate was neutral, and then dried at 95°C; the upper and lower surfaces of the dried activated gel were cut off, and then pressed into sheets under 10 MPa to obtain a carbon electrode aerogel material.
[0076] The dosage and specific parameters of some raw materials are shown in Table 1.
[0077] Table 1
[0078]
[0079] Example 3
[0080] Except that the activation temperature is 800°C, the rest is the same as Example 2.
[0081] Comparative Example 4
[0082] Except that the activation temperature is 400°C, the rest is the same as Example 2.
[0083] Comparative Example 5
[0084] Except that the concentration of potassium hydroxide solution is 30wt%, the rest is the same as Example 2.
[0085] Comparative Example 6
[0086] Except that the amount of animal protein foaming agent is 0.6 g, the rest is the same as Example 2.
[0087] Comparative Example 7
[0088] Except that the amount of animal protein foaming agent is 0.05g, the rest is the same as Example 2.
[0089] Examples 4 to 6 and Comparative Examples 8 to 14
[0090] The carbon electrode aerogel material and the aluminum foil are laminated and then pressed at 20 MPa to form an electrode. In the electrode, the thickness of the carbon electrode aerogel material layer is 50 μm, and the thickness of the aluminum foil is 12 μm.
[0091] The selection of carbon electrode aerogel materials and the specific capacitance of the electrode are shown in Table 2.
[0092] Table 2
[0093]
[0094] Comparative Example 15
[0095] A highly conductive activated carbon electrode was prepared according to the method of Example 4 of CN105448540A. The specific capacitance was tested to be 174 F / g.
[0096] Comparative Example 16
[0097] An activated carbon / carbon nanotube composite aerogel electrode material was prepared according to the method of Example 1 of CN103050294A. The specific capacitance obtained by testing was 211 F / g.
[0098] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a carbon electrode aerogel material, characterized in that: The steps include: (1) stirring and foaming a raw material containing carbon nanotubes, activated carbon, graphene oxide, a reducing agent, an animal protein foaming agent and water to obtain a foam; keeping the foam at 70 to 120° C. to obtain a wet gel; and freezing the wet gel to obtain a dry gel; The mass ratio of carbon nanotubes, activated carbon and graphene oxide is 1:(20-28):(0.7-1.6), and the mass ratio of graphene oxide to animal protein foaming agent is 1:(0.3-0.8); (2) The dried gel is immersed in a potassium hydroxide solution with a concentration of 3 to 25 wt %; after drying, it is activated at 450 to 850° C. in an inert atmosphere to obtain a carbon electrode aerogel material.
2. The preparation method according to claim 1, characterized in that: The reducing agent is ascorbate, and the mass ratio of graphene oxide to the reducing agent is 1:(1-3); In the raw material of step (1), the amount of graphene oxide used is 0.3 to 0.9 g based on 100 mL of water.
3. The preparation method according to claim 1, characterized in that: The diameter of carbon nanotubes is ≤15nm, and the length of carbon nanotubes is 5-15μm; the specific surface area of activated carbon is 1500-2500m 2 / g, the pore volume of activated carbon is 0.8-1.2mL / g; the oxygen-carbon molar ratio of graphene oxide is 0.45-0.65, the sheet diameter of graphene oxide is 15-50μm, and the sheet thickness of graphene oxide is ≤10nm.
4. The preparation method according to claim 1, characterized in that: In step (1), the insulation time is 3 to 9 hours, and the freezing temperature is -30 to -5°C.
5. The preparation method according to claim 1, characterized in that: In step (2), the dried gel is washed and then immersed in a potassium hydroxide solution; the drying temperature is 70 to 105°C.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The following steps are also included: The activated gel obtained by activation is washed with water and then dried; the dried activated gel is pressed into sheets under the condition of 5-20 MPa to obtain a carbon electrode aerogel material.
7. A carbon electrode aerogel material, characterized in that: The carbon electrode aerogel material is prepared by the preparation method according to any one of claims 1 to 6.
8. An electrode, characterized in that: The electrode comprises a current collector layer and a carbon electrode aerogel material layer formed of the carbon electrode aerogel material according to claim 7, wherein the carbon electrode aerogel material layer is attached to a surface of the current collector layer.
9. The electrode according to claim 8, characterized in that The current collector layer is aluminum foil.
10. The method for preparing an electrode according to claim 8 or 9, characterized in that: The steps include: The carbon electrode aerogel material is laminated to the current collector and then pressed to obtain an electrode.
Citation Information
Patent Citations
Preparation method of active carbon / carbon nano tube composite aerogel electrode material
CN103050294A
Super-capacitor high-conductive active carbon electrode manufacturing method
CN105448540A
Preparation method of graphene / active carbon composite film
CN106531459A